2018
DOI: 10.2807/1560-7917.es.2018.23.3.17-00163
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and seasonality of respiratory syncytial virus hospitalisations in young children in Denmark, 2010 to 2015

Abstract: For future decisions on respiratory syncytial virus (RSV)-vaccination strategies and implementation into national immunisation-programmes, we used national registry data (hospitalisation, microbiology and vital statistics) to determine the age-specific incidence and direct medical costs of annual RSV-associated admissions in children < 5 years-old for the period of 2010–2015. We identified ca 2,500 RSV-associated hospitalisations annually amounting to total direct medical-costs of ca EUR 4.1 million per year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
39
2
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 48 publications
13
39
2
2
Order By: Relevance
“…Most RSV‐associated hospitalisations are of children under 6 months of age; published rate estimates range from 1700 to 4590 per 100 000 population, depending on the study population and methodology . It has been reported that there are more RSV‐associated hospitalisations of young Australian children than influenza‐associated hospitalisations .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most RSV‐associated hospitalisations are of children under 6 months of age; published rate estimates range from 1700 to 4590 per 100 000 population, depending on the study population and methodology . It has been reported that there are more RSV‐associated hospitalisations of young Australian children than influenza‐associated hospitalisations .…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of our study was that we estimated RSV‐associated hospitalisation rates on the basis of RSV‐specific ICD codes, an approach that can underestimate the pathogen‐specific disease burden of respiratory infections . Diagnostic codes other than RSV‐specific codes have also been assigned to RSV‐associated hospitalisations .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in Nordic countries, biennial epidemiological pattern is typical with a large epidemic every 2 years alternating with a minor one. This kind of biennial seasonality has been reported, in addition to Nordic countries, in Croatia and Germany …”
mentioning
confidence: 99%